2012
DOI: 10.1590/s1517-83822012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the composition of culture medium for yeast biomass production using raw glycerol from biodiesel synthesis

Abstract: The work herewith investigated the production of yeast biomass as a source of protein, using Yarrowia lipolytica NRRL YB-423 and raw glycerol from biodiesel synthesis as the main carbon source. A significant influence of glycerol concentration, initial pH and yeast extract concentration on biomass and protein content was observed according to the 2v5-1 fractional design. These factors were further evaluated using a central composite design and response surface methodology, and an empirical model for protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…For reactivation of stock cultures, transfers to tubes containing the same medium were made and the tubes were incubated for 48 h at 25°C. They were scraped with 10 mL of 0.1% (w/v) peptone diluent for each tube and transferred to 500 mL Erlenmeyer flask (Santos et al, 2012) containing YM medium (3 g/L yeast extract; 3 g/L malt extract; 5 g/L peptone; and 10 g/L glucose) and incubated under the same conditions.…”
Section: Microorganism Maintenance and Reactivationmentioning
confidence: 99%
“…For reactivation of stock cultures, transfers to tubes containing the same medium were made and the tubes were incubated for 48 h at 25°C. They were scraped with 10 mL of 0.1% (w/v) peptone diluent for each tube and transferred to 500 mL Erlenmeyer flask (Santos et al, 2012) containing YM medium (3 g/L yeast extract; 3 g/L malt extract; 5 g/L peptone; and 10 g/L glucose) and incubated under the same conditions.…”
Section: Microorganism Maintenance and Reactivationmentioning
confidence: 99%
“…The composition of the production medium using S. salmonicolor (Valduga et al, 2009(Valduga et al, , 2014 and for S. pararoseus (Cabral et al, 2011). This methodology is also applied to obtain other bioproducts, such as biomass (Santos et al, 2012), galacto-oligosaccharides (Lisboa et al, 2012a;Lisboa et al, 2012b), dairy drinks (Martins et al, 2011;Martins et al, 2012;Burkert et al, 2012), enzymes (Maldonado et al, 2012;Campello et al, 2012;Alves et al, 2010), synthesis of natural flavors (Anschau et al, 2011;Aragão et al, 2011), phycocyanin (Moraes et al, 2010) and rhamnolipids (Rosa et al, 2010).…”
mentioning
confidence: 99%
“…Kurcz et al (2018) also reported a significant influence of glycerol concentration on biomass and crude protein production by Candida utilis. Dos Santos et al (2012) observed the concentration of crude glycerol had significant effect only on the biomass production by Yarrowia lipolytica NRRL YB-423, but did not have a significant effect for crude protein production.…”
Section: Design (Ccd)mentioning
confidence: 93%